Decorating Cu2O with Ni-doped metal organic frameworks as efficient photocathodes for solar water splitting. (26th May 2023) - Yu, Run; Chen, Qianqiao; Li, Wenhua; Yu, Xinyuan; Zhong, Qin
Abstract: Severe photocorrosion and fast photoexcited charges recombination hinder the application of Cu2 O in photoelectrochemical (PEC) water splitting. In this work, Ni-doped metal-organic frameworks is firstly applied to improve the performance of electrodeposited Cu2 O. A decorative layer of Ni-doped Cu3 (BTC)2 (Ni-CuBTC) was in-suit constructed on Cu2 O through solvothermal followed by ion-exchange. Cu2 O/Ni-CuBTC photocathodes increase absorption edge to ∼800 nm, positive shift flat band position to 0.4 V, and decrease Tafel value to 74 mV/dec. These results confirm the decorative layer can extend light absorption, facilitate photoexcited charge separation and transfer, and enhance HER activity. A photocurrent density of −1.51 mA/cm 2 at 0 VRHE is obtained with the decoration of Ni-CuBTC, which is 3.4 times of pristine Cu2 O photocathode. Here, the PEC water splitting performance of electrodeposited Cu2 O has been significantly improved with noble-metal-free decorations, which provides a new idea for solving the defects of Cu2 O based photocathode. Graphical abstract: Image 1 Highlights: Ni-CuBTC decorated Cu2 O as HER photocathode by solvothermal and ion-exchange. CuBTC can adjust the energy band structure and promote charges transfer. HER kinetics can be improved with Ni doping. Noble-metal-free Ni-CuBTC acts as co-catalyst, photosensitizer, and protector. It exhibits 3.4 times current density of bare Cu2 O with −1.51 mA/cm 2 at 0 VRHE .